Effectiveness of Olson's Enrichment Training Program and Johnson's Relationship Enrichment on Emotion Regulation and Empathy in Maladjusted Couples - Marzieh Zolfaghari Kahkesh; Masoud Shahbazi; Amin Koraei; Seyedeh Zahra Alavi (Gonabad University of Medical Sciences, 2022)
Background: Developing and promoting empathy between couples can help them deal with destructive communication patterns, increase their satisfaction through effective dialogue and conversation, and, as a result, create a safe place to meet emotional needs. The present study aimed to determine the effectiveness of Olson's enrichment training program and Johnson's relationship enrichment on emotion regulation and empathy in maladjusted couples in Ahvaz City, Iran. Methods: This study was a quasi-experimental pretest-posttest design with a control group. The research population included all maladjusted couples who were referred to Ahvaz's counseling centers in 2021. Among them, 45 couples meeting the inclusion criteria were selected via the convenience sampling method. The participants were randomly assigned to two experimental groups and one control group (n=15). The first experimental group participated in eight 90-minute sessions of Olson's enrichment training program, the second experimental group attended eight 90-minute sessions of Johnson's relationship enrichment, and the control group received no intervention during this time. The participants responded to the difficulties in the emotion regulation scale (DERS) and basic empathy scale (BES-A). The data were analyzed using multivariable analysis of variance (MANCOVA) and Bonferroni post hoc test in SPSS software, version 26. Results: The results suggested that Olson's couple enrichment training and Johnson's training model improved emotion regulation and marital empathy in the couples. The results demonstrated that Johnson's approach was more effective than Olson's approach in improving couples' empathy (P<0.001). Conclusion: Olson's enrichment training program and Johnson's relationship enrichment were effective in improving emotion regulation and marital empathy among maladjusted couples. Therefore, Olson's enrichment training program and Johnson's relationship enrichment workshops can effectively help maladjusted couples mitigate emotional problems.